Results of salmon fishery in the Far-Eastern fishery basin in 2023 - A. N. Kanzeparova; I. A. Vaizova; A. I. Nikiforov; V. A. Belyaev (Известия ТИНРО, 2024)
Data on forecasted catch, actual catch and their ratio for the main species of pacific salmon are presented; the salmon fishery in the Far Eastern fishery basin in 2023 is analyzed; the reasons for discrepancy between the actual catches of pacific salmon and forecast expectations are discussed.